(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The objective of the present work is to formulate etoricoxib (EtR) cyclodextrin complexes by using ternary systems as citric acid, Tartaric acid and PVP K-30 in order to enhance solubility and evaluate the enhanced solubility by in-vitro dissolution. The inclusion complexes were prepared by spray drying method and the stability constants of the formed complexes were calculated from the phase solubility studies. The formulated complexes were evaluated for drug release by in-vitro dissolution. The prepared complexes were confirmed and characterized by FT-IR, DSC, XRD, SEM and in-vitro dissolution. The stability constant K (1:1) of EtR- βCD-PVP-K30 (1:1:2%) and EtR- HPβCD-PVP-K30 (1:1:2%) complex was found to be 57.56 mol-1 and 360.01mol-1. Phase solubility studies of each type was found to be of AN type. The release of Etoricoxib from complexes prepared with hydroxy propyl β-cyclodextrin (HPβCD) and citric acid (Cit) at the ratio of 1:1:2 M by lyophilization method shows a drug release 100.85 ± 4.34 %, significantly higher than other cyclodextrin ternary complexes.